Inflammatory Markers and Duration of Symptoms Have a Close Connection With Diagnosis and Staging of Acute Appendicitis in Children - Lan, Jiaming; Zhu, Hai; Liu, Qingshuang; Guo, Chunbao (Frontiers in Pediatrics, 2021)
Abstract Background: For children with acute appendicitis (AA), a clear diagnosis is a challenge. The purpose of this study is to explore whether inflammatory markers in the blood combined with symptom duration are helpful in the diagnosis of acute appendicitis and in predicting the severity of acute appendicitis. Methods: All the selected patients underwent appendectomy between November 10, 2011 and November 15, 2019, in whom preoperative WBCC, CRP and NE% had been measured in a short time. All patients were divided into two groups: uncomplicated AA and complicated AA, postoperatively. Results: For our standards, 813 patients were selected, 442 of them are complicated AA. The mean (standard deviation (SD)) age for uncomplicated AA group was 9.78±2.02 years and complicated AA group was 9.69±2.16 years(P=0.55). Elevated WBCC, CRP and NE% had a higher relatively sensitivity in complicated AA than uncomplicated AA. Specially, when WBCC, CRP and NE% are at normal level, which had a sensitivity of 100% in uncomplicated AA. But there were only 9 patients. CRP values were significantly different in three time groups, whether uncomplicated or complicated AA. Conclusion: The combination of WBCC, CRP and NE% values is very sensitive for the diagnosis of acute appendicitis. And when we predict complicated AA with CRP value, we also need to consider the time of symptom onset.